Moluscos continentales de México: Dulceacuícolas - Naranjo García, Edna (2003)
There are 16 freshwater mollusc families reported from Mexico, but besides a few studies of habitat and distribution, only Pomacea flagellata, Pomacea patula catemacensis and Helisoma trivolvis has been studied in some detail, mainly regarding reproduction. In Mexico, the parasite Fasciola hepatica is transmitted by Lymnaea obrussa, L. humilis and L. cubense). Larval trematodes have been found in Planorbidae, Physidae, Lymnaeidae, Ancylidae and Pisidiidae. Diet and growth have been studied for Lymnaea bulimoides, L. cubensis and L. humilis. Piquerol A extracted from Piqueria trinervia acts as molluscicide. There are reports about freshwater molluscs as pollution bioindicators and as source of food, foreing currency and lime. Mexican freshwater molluscs are an endangered resource.